Group filial therapy : the complete guide to teaching parents to play therapeutically with their children - Guerney, Louise F. (Louise Fisher), 1928-; Ryan, Virginia (Jessica Kingsley Publishers, 2013)
In Group Filial Therapy (GFT), therapists train parents to conduct play sessions with their children. This book provides an accessible guide to the theory and practice of GFT, and for the first time offers step-by-step guidelines for implementing the GFT program developed by Dr Guerney.